From Disruption to Adaptation: Drivers and Implicationsof ‎Change Readiness in Changing Times - Tiwari , Dr. Nilesh Kumar; Pahwa, Dr. Mohit; Azad, Dr. Shivam (International Journal of Accounting and Economics Studies, 2025)
Change is the law of nature. The Covid-19 pandemic has called on firms and their organizations to adapt and manage in new ways. organizations faced massive strain to adapt to business operations, prompting a rapid shift to remote work for most of employees. To ensure sustainability and continued growth, business has to swiftly configure their processes and embrace new operational models. Increased ‎capacity for organizations to expand resources and preparedness for this new change is needed. As human resources executives, it is crucial ‎to keep people prepared to adapt and effectively execute improvements. In this conceptual article, we review the notion of individual Readi-‎ness for organizational change. The literature review indicates that by engaging in decision-making and communicating explicit and regularly ‎new improvements and giving learning or development opportunities, people are more inclined to improve their organizations (drivers to ‎cultivate a readiness to change). The authors have also discussed the outcomes (building capabilities, change-supportive behavior, and in-‎creasing efficiency of the organization's individuals) of cultivating Readiness to change‎.
Keywords: Active Participation; Communication; Learning Culture; Organization Change; Readiness to Change